Training Business Strategy and Tax on CV. Inara - Harahap, Arman (CV. Inara, 2022)
Strategy is needed in an organization to develop the organization. One strategy that has been developed is related to recording to financial reporting and planning to tax calculation. Transparent financial report will be very useful, especially when it is related to decision making for organizational development. Besides, financial report also becomes the basis in the calculation and reporting of income tax (PPh) of the organization. Training in financial reporting and tax accounting planning will greatly assist the organization, both for decision making and corporate strategic planning. Business strategic training, financial reporting, and taxation are conducted to help CV Inara in achieving better business performance.